Synchrony, Science and the ‘Relativity of Facts’ - Boardman, Gareth Ernest (Cosmos and History: The Journal of Natural and Social Philosophy, 2020)
This is an analysis of the validity, and assertion of scientific value, of Einstein’s 1905 claimed discovery denoted "the relativity of simultaneity.”